2013
DOI: 10.1021/om3011307
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of CO2 and CS2 with [RuH(η2-CH2PMe2)(PMe3)3]

Abstract: Carbon disulfide reacted with the cyclometalated ruthenium complex [RuH(η 2 -CH 2 PMe 2 )(PMe 3 ) 3 ] (1) at low temperature to yield the dithioformate complex [Ru(η 1 -SC(S)H)(η 2 -CH 2 PMe 2 )(PMe 3 ) 3 ] (4), where the CS 2 inserts into the metal hydride bond. On warming, complex 4 rearranges to give the known complex [Ru(S 2 CHPMe 2 CH 2 -κ 3 S,S,C)(PMe 3 ) 3 ] (3), where the CS 2 is inserted in a metal phosphorus bond. Further reaction of this complex with excess CS 2 over a period of days resulted in in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Although the insertion reaction was more facile for the Ru–H bond than Ru–C, a thermodynamically stable Ru–C-inserted product trans -[Ru(DMPE) 2 ­(O 2 ­CMe)(H)] was observed, suggesting a rapid deinsertion of CO 2 from trans -[Ru(DMPE) 2 (Me)(O 2 CH)], the Ru–H-inserted product. In a similar study using a cyclometalated [RuH(η 2 -CH 2 PMe 2 )(PMe 3 ) 3 ] complex, Field et al reported the relative reactivity of the Ru–H and Ru–C bonds with respect to CO 2 insertion . They found that CO 2 inserts into the Ru–C bond with the apparent absence of any observable CO 2 insertion into the Ru–H bond.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Although the insertion reaction was more facile for the Ru–H bond than Ru–C, a thermodynamically stable Ru–C-inserted product trans -[Ru(DMPE) 2 ­(O 2 ­CMe)(H)] was observed, suggesting a rapid deinsertion of CO 2 from trans -[Ru(DMPE) 2 (Me)(O 2 CH)], the Ru–H-inserted product. In a similar study using a cyclometalated [RuH(η 2 -CH 2 PMe 2 )(PMe 3 ) 3 ] complex, Field et al reported the relative reactivity of the Ru–H and Ru–C bonds with respect to CO 2 insertion . They found that CO 2 inserts into the Ru–C bond with the apparent absence of any observable CO 2 insertion into the Ru–H bond.…”
Section: Introductionmentioning
confidence: 97%
“…They found that CO 2 inserts into the Ru–C bond with the apparent absence of any observable CO 2 insertion into the Ru–H bond. It again suggests that metal hydride insertions and subsequent decarboxylation are too fast to observe on the NMR time scale …”
Section: Introductionmentioning
confidence: 99%
“…The "weak point" in the apparently unscratchable robustness of carbon dioxide is the susceptibility to nucleophilic attacks at the carbon atom [22][23][24]. Thus, a range of nucleophilic reagents, including neutral N-heterocyclic carbenes [25,26], are known to react with CO 2 even under mild conditions, and some chemistry at transition metal centers is provided by the possibility of CO 2 insertion into the bond between a metal atom and a suitable anionic ligand, e.g., alkyl, allyl, alkoxide and hydride [27][28][29][30][31][32]. In this context, amines are key reactants towards carbon dioxide, and indeed carbon dioxide/amine systems have been intensively investigated in the field of capture/storage [33][34][35] and exploited for the incorporation of the CO 2 moiety within organic structures [36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%
“…In this context, Jagirdar’s group demonstrated the insertion of CS 2 into one of the Ir-H bonds in [Ir(H) 5 (PCy 3 ) 2 ] to afford the dihydrido dithioformate complex cis -[Ir(H) 2 ( ƞ 2 -S 2 CH)(PCy 3 ) 2 ] ( A ), accompanied by the elimination of H 2 [ 7 ]. Similarly, the cyclometalated ruthenium complex [Ru(S 2 C(H)PMe 2 CH 2 - κ 3 S,S,C)(PMe 3 ) 3 ] was shown to react with an excess of CS 2 , which undergoes a second insertion into a Ru–S bond to yield [Ru(SC(=S)SCH(–S)PMe 2 CH 2 - κ 3 S,S,C)(PMe 3 ) 3 ] ( B ) [ 8 ]. Wang and coworkers reported the disproportionation of CS 2 when reacted with the Me 2 C and Me 2 Si doubly bridged bis(cyclopentadienyl) dinuclear molybdenum carbonyl complex (Me 2 C)(Me 2 Si)[( ƞ 5 -C 5 H 3 )Mo(CO) 3 ] 2 , which led to the formation of complex C [ 9 ].…”
Section: Introductionmentioning
confidence: 99%